1983
DOI: 10.1128/mcb.3.5.829
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the adenovirus E1Aa protein, a positive-acting transcriptional factor, in infected cells infected cells.

Abstract: The function of the adenovirus E1Aa protein (the product of the 13S ElA mRNA) during a productive viral infection is to activate transcription of the six early viral transcription units. To study the mechanism of action of this protein, a peptide which was 13 amino acids long and had a sequence unique to the protein product of the adenovirus 13S ElA mRNA (pElAa) was coupled to keyhole limpet hemocyanin and used to raise an antibody in rabbits. The resulting antiserum was specific to this protein and did not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
55
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 50 publications
10
55
0
Order By: Relevance
“…These results are in general agreement with a number of recently published reports Yee et al, 1983;Feldman & Nevins, 1983) in which it was shown, using mainly immunofluorescence techniques, that in Ad-5-infected cells most of the Ela proteins and the Elb 58K protein were located in the nucleus and cytoplasm. Previous immunofluorescence studies in our laboratory using TBS have also suggested a distribution of Ad-12 52K and 41K proteins similar to that obtained with the subcellular fractionation (P. H. Gallimore, unpublished results).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in general agreement with a number of recently published reports Yee et al, 1983;Feldman & Nevins, 1983) in which it was shown, using mainly immunofluorescence techniques, that in Ad-5-infected cells most of the Ela proteins and the Elb 58K protein were located in the nucleus and cytoplasm. Previous immunofluorescence studies in our laboratory using TBS have also suggested a distribution of Ad-12 52K and 41K proteins similar to that obtained with the subcellular fractionation (P. H. Gallimore, unpublished results).…”
Section: Discussionsupporting
confidence: 82%
“…However, our inability to demonstrate significant levels of 41K protein associated with the chromatin possibly indicates that such an interaction may not occur in ~,ivo. This is supported by the observations of Feldman & Nevins (1983) who found in Ad-5-infected cells that the portion of the Ela protein present in the nucleus co-purifies with the nuclear matrix.…”
Section: Discussionsupporting
confidence: 78%
“…These include the internal chromosomal scaffold proteins (29), the well-characterized lamin proteins which underlie the nuclear envelope (20)(21)(22), tight DNA-binding proteins (8,35), and certain DNA tumor virus-transforming proteins, such as simian virus 40 and polyomavirus large T antigens (9,40,44), adenovirus ElAa (19), and herpesvirus ICP8 proteins (33). Our .…”
Section: Downloaded Frommentioning
confidence: 99%
“…We speculate that p64 and p67 may be derived from these RNA species by an internal splice site within one of the coding exons in a manner similar to that described for the adenovirus Ela gene (42). Interestingly, Ela proteins also have short half-lives of 30 to 45 min (K. R. Spindler and A. J. Berk, submitted for publication) and are also tightly bound to the cell nucleus (16).…”
mentioning
confidence: 99%